Experimental Investigation on Electrochemical Grinding (ECG) for Stainless Steel 316 - Abdullah J. Ghadban; Abbas F. Ibrahim (Engineering and Technology Journal, 2020)
This research focuses on material removal rate (MRR) and surface roughness during electrochemical grinding (ECG) for stainless steel 316. The effect of applied current, electrolyte concentration, gap size and spindle speed on machining performances has been studied. Where applied current used are (10, 20, 30, 40) A, electrolyte concentration used (100, 150, 200, 250) g/l, gap size used (0.2, 0.3, 0.4, 0.5) mm and spindle speed used (75, 150, 180, 280) rpm. Through the Taguchi design based experimental study the characteristic features of the ECG process are discussed. Where the maximum MRR can be obtained at 40 A of the current, 250 g/l of the concentration, 0.2 mm of the gap and 180 rpm of spindle speed. The best surface roughness can be obtained at 10 A of the current, 200 g/l of the concentration, 0.4 mm of the gap and 280 rpm of spindle speed..